Urban Rehabilitation, Social Innovation, and New Working Spaces in Lisbon - Sofia Morgado (MDPI AG, 2021)
This study brings together three subjects: urban rehabilitation, social innovation, and new working spaces, envisaging an intersectoral viewpoint, focusing on a European city, Lisbon, arguing that the public sector holds the capacity to consistently drive positive achievements in this respect. This study involves analyzing policy, governance, and urban planning documents in force, observation and spatial analysis using open-source databases, and stakeholder interviews. The result is in line with the primary research plea applied to the case study, and conclusions show that public intervention, whenever applied systematically from the city vision to local plans, resorting to close bonds between the sites and the communities in a participatory and collaborative way, may lead to urban rehabilitation and social innovation through the inception and development of new working spaces. The study was designed while researching as a member of COST CA18214 (The Geography of New Working Spaces and the Impact on the Periphery).